Development of Microalgae Growth Monitoring System Using TSD-10 Sensor and ThingSpeak Platform - I Dewa Made Subrata; Mulki Azmi Novrizal (The University of Lampung, 2024)
Microalgae chlorella sp. is one of the low-level plants that has many benefits and need to be harvested when they have reached optimum density. This study aims to develop a microalgae density monitoring system using the TSD-10 sensor and the ThingSpeak platform. The output voltage from the TSD-10 sensor was calibrated into microalgae density using hemocytometer and then sent wirelessly to the ThingSpeak cloud server using the ESP8266 module. A linear equation of y = –1.633 x +1421.3 was obtained from the calibration process where y is microalgae density (cell/ml) and x is analog to digital conversion (ADC) value of the TSD-10 sensor. The determination coefficient of the calibration and validation process is 0.9921 and 0.938 respectively. The measurement stability was quite good with a standard deviation ranging from 1.15×104 cell/ml to 2×104 cells/ml of culture medium. The measurement accuracy of the validation process using the RMSE (Root Mean Square Error) formula is 3.25. The time response of the sensor after power on is 5.85 s and the time it takes to display data on the ThingSpeak cloud is 16.03 s. Thus the measuring instrument developed can be said to have a fairly good performance. Keywords: Density monitoring, Microalgae, ThingSpeak platform, Tsd-10 sensor.